(untitled) (Journal of Lithic Studies, 2016)
The stone knapping industry is largely unknown from Galician Iron Age hillforts. Research into the material culture of these settlements is increasingly diverse, meaning this research is no longer reduced to techno-typological studies of pottery and metals, but also includes a wide range of approaches, including anthracological and carpological analyses, macrolithic tools, and so on. However, there have still been no studies on knapped stone tools. This gap in the research, which may be dependent on various factors, limits the overall perception of the economy of these communities. In this paper we present the data obtained from a use-wear study of a rock crystal tool from the O Achadizo hill fort (Boiro, A Coruña, Galicia). This tool was located in shell midden A, dated as Second Iron Age, and is of particular importance because of its pointed morphology and the configuration evidence on its perimeter. We carried out a macroscopic and microscopic analysis to obtain as much data on this piece as possible. Macroscopically we identified retouching as well as an impact fracture, and at the microscopic level we found several series of striations on the ventral face which are not in keeping with the use of the piece as a projectile tip. We decided to generate several “gigapixel” images of different areas of the tool, in order to record the order and arrangement of these striations, and to understand their origin. We identified differential orientation of the striations in the various sectors of the tool, suggesting a technical origin. The combination of the macro and microscopic analysis of both faces has allowed us to functionally interpret the tool as a sharp element.